Wireless Technology: Protocols, Standards, and Techniques - Yacoub, Michel Daoud (CRC Press LLC, 2011)
Vast, complex technologies, countless relevant topics, seemingly limitless documentation of standards and recommendations… In a field as dynamic as wireless technology, how is one to keep up when the very task of deciding which publications to read and which resources belong on your shelf can be daunting?